Representação de skatistas mulheres na produção audiovisual de Crystal Moselle : análise de Skate Kitchen e Betty - Zumerle, Julia Tiengo (2023)
This research aims to analyze the representation of female skateboarders in the film Skate Kitchen (2018) and in the narrative series Betty (2020), by filmmaker Crystal Moselle. The theoretical reference works include the concept of genre (Scott, 2017; Butler, 2018) and the understanding of cinema as a genre technology (Lauretis, 1987). Guided by the axes of gender, skateboarding and city, constantly used in the narratives, a film analysis of images and sounds was carried out based on the methodological framework presented by Manuela Penafria (2009). The corpus of analysis consists of a fictional feature film and six consecutive episodes from the first season of the series. The observations presented extracted in the analysis highlight the claim of the creative, transgressive and non-hierarchical ethos of skateboarding by groups initially marginalized and insert Moselle's works in the context of representing the experiences of female skateboarders and their non-conformative practices to explore fun and freedom of the skateboarding experience